Accuracy of a smartphone to test laryngoscope's light and an audit to our laryngoscopes using an ISO standard - Machado,Diogo Alcino de Abreu Ribeiro Carvalho (2017)
Abstract Background and objectives: Laryngoscope is a key tool in anesthetic practice. Direct laryngoscopy is a crucial moment and inadequate laryngoscope's light can lead to catastrophic consequences. From our experience laryngoscope's light is assessed in a subjective manner and we believe a more precise evaluation should be used. Our objective is to compare the accuracy of a smartphone compared to a lux meter. Secondly we audited our Operating Room laryngoscopes. Methods: We designed a pragmatic study, using as primary outcome the accuracy of a smartphone compared to the lux meter. Further we audited with both the lux meter and the smartphone all laryngoscopes and blades ready to use in our Operating Rooms, using the International Standard form the International Organization for Standardization. Results: For primary outcome we found no significant difference between devices. Our audit showed that only 2 in 48 laryngoscopes complied with the ISO norm. When comparing the measurements between the lux meter and the smartphone we found no significant difference. Discussion: Ideally every laryngoscope should perform as required. We believe all laryngoscopes should have a practical but reliable and objective test prior to its utilization. Our results suggest the smartphone was accurate enough to be used as a lux meter to test laryngoscope's light. Audit results showing only 4% comply with the ISO standard are consistent with other studies. Conclusion: The tested smartphone has enough accuracy to perform light measurement in laryngoscopes. We believe this is a step further to perform an objective routine check to laryngoscope's light.